Core Practices as an opportunity for networking during the practical semester - Schellenbach-Zell, Judith; Ritter, Roswitha; Sommer, Sarah; Fussangel, Kathrin (Swiss Journal of Educational Research, 2023)
Incoherencies at different points in teacher education lead to the fact that students are confronted with the challenge to bring their previous university acquired knowledge from the specialised sciences, subject didactics and educational sciences in practical phases in connection with the classroom events. In this conceptually oriented contribution, we argue for the approach of so-called Core Practices and explore the extent to which this approach – especially by connecting it with current research perspectives – holds potential for networking at various levels, especially in the context of university-based practical phases.